Recently emerged and future water-scarce countries (based on less than 1 000 m3 available per person per year) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Since 1955Bahrain, Barbados, Djibouti, Jordan, Kuwait, Malta, SingaporeSince 1990Algeria, Burundi, Cape Verde, Israel, Kenya, Malawi, Qatar, Rwanda, Saudi Arabia, Somalia, Tunisia, United Arab Emirates, YemenBy 2025Comoros, Egypt, Ethiopia, Haiti,...